A Novel Trust Evaluation Mechanism for Edge Device Access of the Internet of Things. (9th August 2022) - Feng, Xiao; Yuan, Zheng
Abstract : The purpose of this paper is to build a novel trust evaluation mechanism model for edge devices of the Internet of Things (IoT). First, we use the SM9 authentication mechanism to authenticate the identity of the terminal device. Authentication includes both single-domain and cross-domain authentication of devices, reducing the time overhead of the authentication process. Then, we use the satisfaction function and the time degradation factor to improve the direct trust in the behavioural trust of Bayesian equations. Next, the weight of indirect trust of each device is calculated to improve the gray association method, and the accuracy of indirect trust is improved. Finally, the trust value of the edge device is obtained by combining the authentication result and the behaviour trust. Simulation results verify that the trust evaluation model proposed in this paper has certain advantages for the reliability, accuracy, and efficiency of trust evaluation.